Strategies and Management for Psychiatric Drug Withdrawal: A Systematic Review of Case Reports and Series - Eserian, Jaqueline K.; Blanco, Vinícius P.; Mercuri, Lucildes P.; Matos, Jivaldo R.; Kalleian, Eugênia A.; Galduróz, José C. F. (Pharmacopsychiatry, 2024)
In recent years, an increasing number of case reports on psychiatric drug withdrawal have emerged, offering detailed clinical insights and valuable real-world evidence on the withdrawal process. The objective of this review was to evaluate the strategies and management for withdrawing psychiatric drugs, as detailed in case reports and series. A systematic review of case reports and series published between 2013 and 2023 was conducted to capture the latest trends in psychiatric drug withdrawal. Cases were identified following the PRISMA guidelines by searching electronic databases Medline and Scopus. Finally, 47 case reports and series were included. The primary reason for drug withdrawal was attributed to the emergence of adverse events, followed by medication dependence or abuse, and clinical decision-making or symptom resolution. Gradual reduction of doses was implemented through various management approaches as the primary strategy for drug withdrawal, and drug substitution emerged as the second most employed strategy. Also, patients were mostly undergoing polypharmacy. Favorable treatment outcomes were reported in the majority of cases, suggesting that psychiatric drug withdrawal is feasible – though quite challenging in some situations. However, the remarkably low number of unsuccessful cases may create a misleading impression of the significant difficulty associated with withdrawing psychiatric drugs.
Keywords: drug tapering; dose reduction; drug therapy; psychoactive drug; drug withdrawal symptoms